Answer:
x =
![(2)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9l76ru6jxv4fv4b8lpmxx1u47fxut8ydly.png)
Explanation:
x - 5 ( x - 1 ) = x - ( 2x - 3 )
![x -5(x-1 )= x+[-1(2x-3)]](https://img.qammunity.org/2022/formulas/mathematics/high-school/k5wkvsmekhnlx6l07v1vjjob6ci1cbox06.png)
Expand them.
![x-5x+5=x+[-2x+3 ]](https://img.qammunity.org/2022/formulas/mathematics/high-school/hk686322vtycooamt4ierf8r3lrxw9o5fy.png)
![x-5x+5=x-2x+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/2dy8zre6crw7rnh7vtrschk42j2a7alsvt.png)
Group Like terms :
![-4x+5=-x+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/bj2co90v92x3e96yq7vumzi5m3l3ctz1l9.png)
Make X the subject : ( Move terms )
![-4x+x=-5+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/ta1unk0il80364tm9yov55sh907c2h9uyu.png)
![-3x=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/hz4c5l1q14ui0nnp1jng7aru4euppaw14q.png)
![(-3x)/(-3) =(-2)/(-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/x7jbvh2cfic4erpxhn46e4blfanv7kka8i.png)
![x=(2)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rhcozk0cgaphq2qobmrlf83roc83h2lcrv.png)
And the answer would be
.
Hope the answer helped :)
Sorry for the delay saw a mistake and have to retype the whole thing again :I